Promoting and developing knowledge communities in the workplace - Azizan, Norizan; Yusof, Ab. Aziz (Perpustakaan Sultanah Zanariah, 2001)
Knowledge is a critical resource for competing in today's economy. 'Today's organizations must find ways to turn the knowledge of their employees into a competitive advantage in order to survive and succeed. It is very critical that the relevant people are well-equipped with the necessary knowledge and know how in order to cope effectively and efficiently particularly when making decisions that affect their lives as well as the lives of others. Thus, continuous enhancement to their knowledge, skills and abilities is a must. However, companies are in danger of losing critical organizational knowledge when workers retire or resign. This paper is focused on promoting and developing knowledge communities or communities of practice in the workplace. The benefits of establishing communities go far beyond retention of knowledge. It is a way of describing how people in organizations can teach and learn from each other. By facilitating the development of communities of practice in the workplace, organizations can help ensure that their human resource is fully and effectively utilized.